2017
DOI: 10.1002/2016ja023728
|View full text |Cite
|
Sign up to set email alerts
|

A multiresolution inversion for imaging the ionosphere

Abstract: Ionospheric tomography has been widely employed in imaging the large‐scale ionospheric structures at both quiet and storm times. However, the tomographic algorithms to date have not been very effective in imaging of medium‐ and small‐scale ionospheric structures due to limitations of uneven ground‐based data distributions and the algorithm itself. Further, the effect of the density and quantity of Global Navigation Satellite Systems data that could help improve the tomographic results for the certain algorithm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…It has been shown that tomographic imaging captures the ionosphere better when an “adequate” and even GPS rays distribution traverses the voxels of the reconstruction grids radially (Chartier et al, ; Spencer & Mitchell, ). Tomographic results using observations from a clustered network of ground stations could also equally capture an “unrealistic” ionospheric structures as those obtained from a scarce distribution of ground stations (Chartier et al, ; Yin et al, ). Yin et al () recently reported the impact of the density of ground stations on tomographic imaging results and revealed that improvements could only be offered when receivers are to within 150 km to 200 km distance from each other.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been shown that tomographic imaging captures the ionosphere better when an “adequate” and even GPS rays distribution traverses the voxels of the reconstruction grids radially (Chartier et al, ; Spencer & Mitchell, ). Tomographic results using observations from a clustered network of ground stations could also equally capture an “unrealistic” ionospheric structures as those obtained from a scarce distribution of ground stations (Chartier et al, ; Yin et al, ). Yin et al () recently reported the impact of the density of ground stations on tomographic imaging results and revealed that improvements could only be offered when receivers are to within 150 km to 200 km distance from each other.…”
Section: Resultsmentioning
confidence: 99%
“…Tomographic results using observations from a clustered network of ground stations could also equally capture an “unrealistic” ionospheric structures as those obtained from a scarce distribution of ground stations (Chartier et al, ; Yin et al, ). Yin et al () recently reported the impact of the density of ground stations on tomographic imaging results and revealed that improvements could only be offered when receivers are to within 150 km to 200 km distance from each other. Furthermore, the authors pointed out that better improvements could be achieved with the inclusion of multiple constellations besides the GPS constellation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…VTEC from MIDAS was computed by vertical integration of the electron density obtained following the above procedure. Detailed theory about MIDAS can be found in a number of literature sources (Bust et al, 2007;Jayawardena et al, 2016;Meggs et al, 2005;Mitchell & Spencer, 2003;Spencer & Mitchell, 2007;Yin et al, 2017) and references therein. For more information about the recent MIDAS algorithm used in this study, readers are referred to Spencer and Mitchell (2007), Giday et al (2016), and Yin et al (2017).…”
Section: Midasmentioning
confidence: 99%